Penerapan Sanksi Adat Terhadap Pelaku Tindak Pidana Zina di Desa Kampung Baru Sentajo Kecamatan Sentajo Raya Kabupaten Kuansing - Tri Ramadhanti; Firdaus '; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Acts of adultery are classified into severe offenses, which violate the family honor and legal interests of a husband and also violate the public interest. And according to custom in Kampung Baru village, the perpetrators of this zina should be given sanction that must be married. Adultery in the Criminal Code of the object is a married man and woman, while in Kampung Baru Village adultery is also committed by unmarried men and women. Therefore, the purpose of this thesis writing, namely: first, knowing custom mechanisms in setting sanctions against perpetrators of adultery in Kampung Baru Village Sentajo Sentajo Raya District Kuansing District; Secondly, to know the values that affect the decision of adat sanction against the adultery in Kampung Baru Sentajo Village Sentajo Raya Sub-district of Kuansing Regency. This type of research can be classified in the type of legal juridical sociological research, because in this study the authors directly conduct research on the location or place studied in order to provide a complete and clear picture of the problem under study. This research was conducted in Kampung Baru Sentajo Village Sentajo Raya Sub-district Kuansing District. Sources of data used, namely: primary data and secondary data. Data collection techniques in this study with Observation, Interview, and Library Studies. The conclusions can be obtained from the first research, customary mechanism in determining sanctions against perpetrators of adultery in Kampung Baru Sentajo Village Sentajo Raya Subdistrict Kuansing District is sitting together, deliberations on the perpetrators of adultery will be nikahkan, giving advice by customary leaders, public figures and figures religion and penalties. Second, the values that influence and become the benchmark of customary adat stakeholders in giving the decision of adat sanction against adultery that has been done by the adultery in Kampung Baru Village Sentajo Sub Sentajo Raya Subdistrict Kuansing Regency that is value of morality, moral value and religion value. Suggestion writer First, For adat stakeholders, religious leaders and community leaders who have authority in controlling the community to be more assertive in determining and deciding sanctions given to the perpetrators of adultery, thus providing a deterrent effect against the perpetrators of adultery. Secondly, for the new village villagers sentajo to strengthen the science of religion in the personality of self, so that with the power of religious values can prevent the act of munkar like the act of adultery. Keywords: Acts of Zina-Customary Law-Desa Kampung Baru Sentajo